TINDAK TUTUR DIREKTIF BAHASA MELAYU PONTIANAK DALAM SITUASI KOMEDI “KELUARGA 69” - Evi Novianti (tuahtalino, 2020)
Pontianak Malay is one of the languages in West Kalimantan. Study of language should be done from various linguistic approaches. One of them is pragmatics. Family 69 is a Pontianak Malay language sitcoms program. This program is broadcast by PONTV. The Malay language used in this event is a portrait of the condition of the Pontianak Malay language used in the speaker community. The problem discussed is the type and form of Pontianak Malay language directive speech in a family situation comedy 69. The approach used in this study is the pragmatic approach. The research method used is descriptive qualitative. The theory used is imperative theory and speech act. The source of the data in this study is directive speech acts in the Family 69 sitcoms broadcast by PONTV. The results of the discussion note that there are six types of directives in the Pontianak Malay language directive in the Family Situation 69 comedy, namely commands, orders, invitations, prohibitions, omissions, and suggestions. The manifestation of the Pontianak Malay language directive speech in the Family Situation 69 comedy is twofold, namely direct and indirect directive speech.